2020
DOI: 10.1073/pnas.1909599117
|View full text |Cite
|
Sign up to set email alerts
|

Consistent scaling of inbreeding depression in space and time in a house sparrow metapopulation

Abstract: Inbreeding may increase the extinction risk of small populations. Yet, studies using modern genomic tools to investigate inbreeding depression in nature have been limited to single populations, and little is known about the dynamics of inbreeding depression in subdivided populations over time. Natural populations often experience different environmental conditions and differ in demographic history and genetic composition, characteristics that can affect the severity of inbreeding depression. We utilized extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 87 publications
(110 reference statements)
1
81
2
Order By: Relevance
“…We have only recently begun to understand the precise consequences of inbreeding for individual fitness in natural populations. In Soay sheep, we found that the odds of survival decreased by 60% with a mere 10% increase in F ROH , adding to a small yet growing body of genomic studies reporting stronger effects of inbreeding depression in wild populations than assumed in pre-genomics times 13 , 14 , 50 , 51 , 53 . Other recent examples include lifetime breeding success in red deer, which is reduced by up to 95% in male offspring from half-sib matings 13 and lifetime reproductive success in helmeted honeyeaters, which is up to 90% lower with a 9% increase in homozygosity 51 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We have only recently begun to understand the precise consequences of inbreeding for individual fitness in natural populations. In Soay sheep, we found that the odds of survival decreased by 60% with a mere 10% increase in F ROH , adding to a small yet growing body of genomic studies reporting stronger effects of inbreeding depression in wild populations than assumed in pre-genomics times 13 , 14 , 50 , 51 , 53 . Other recent examples include lifetime breeding success in red deer, which is reduced by up to 95% in male offspring from half-sib matings 13 and lifetime reproductive success in helmeted honeyeaters, which is up to 90% lower with a 9% increase in homozygosity 51 .…”
Section: Discussionmentioning
confidence: 60%
“…However, individual fitness will be different under natural conditions and consequently, there is a need to study inbreeding depression in wild populations to understand its genetic basis in an evolutionary and ecological context. To date, only a handful of studies have estimated inbreeding depression using genomic data in the wild 13 , 14 , 50 53 . While these studies show that inbreeding depression in wild populations is more prevalent and more severe than previously thought, all of them used genome-wide inbreeding coefficients and did not explore the underlying genetic basis of depression.…”
Section: Introductionmentioning
confidence: 99%
“…The role of deleterious mutations is also increasingly discussed in applied conservation, in particular when considering genetic rescue of small populations (Kyriazis, Wayne, & Lohmueller, 2020;Ralls, Sunnucks, Lacy, & Frankham, 2020). To date, studies in wild populations have mostly focused on average, genomewide fitness effects of deleterious recessive alleles through measuring genome-wide inbreeding coefficients (Bérénos, Ellis, Pilkington, & Pemberton, 2016;Chen, Cosgrove, Bowman, Fitzpatrick, & Clark, 2016;Harrisson et al, 2019;Hoffman et al, 2014;Huisman, Kruuk, Ellis, Clutton-Brock, & Pemberton, 2016;Niskanen et al, 2020), or genome-sequence based predictions of deleterious mutations (Grossen, Guillaume, Keller, & Croll, 2020;Robinson, Brown, Kim, Lohmueller, & Wayne, 2018;Xue et al, 2015). Therefore, we still know very little about how deleterious mutations in different parts of the genome contribute to inbreeding depression, as these analyses usually require large samples of individuals with known fitness and dense genomic data -both of which are scarce in wild non-model organisms.…”
Section: Introductionmentioning
confidence: 99%
“…A key finding in this study is the negative relationship between inbreeding (F ROH ) and survival (Figure 4; Figure ), demonstrating the important connection between genetics and fitness. Some previous studies have used reduced‐representation genome data to test for inbreeding depression in other study systems (Bérénos et al, 2016; Hoffman et al, 2014; Huisman et al, 2016; Niskanen et al, 2020). Our study in combination with these, has important implications for conservation biology as it demonstrates how genomic approaches can effectively detect inbreeding depression in natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical support for a link between genomic inbreeding and fitness was for a long time rare for wild populations. However, developments within the field have recently enabled such studies (Bérénos et al, 2016; Chen et al, 2016; Harrisson et al, 2019; Hoffman et al, 2014; Huisman et al, 2016; Niskanen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%